2014
DOI: 10.1589/jpts.26.1855
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Isometric Knee Extension Muscle Strength Measurements of Healthy Elderly Subjects Made with a Hand-held Dynamometer and a Belt

Abstract: [Purpose] The purpose of this study was to examine the reliability of three isometric knee extension strength measurements (IKE) made with a hand-held dynamometer (HHD) and a belt of healthy elderly living in the community as subjects. [Subjects] The subject cohort consisted of 186 healthy elderly people, aged 65 to 79 years, living in local communities. [Methods] IKE of the leg subjects used to kick a ball was measured. IKE of each subject was measured three times using an HHD-belt at intervals of 30 seconds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
3
40
1
Order By: Relevance
“…Knee extension strength was measured using a hand-held dynamometer (μ-TAS F-1; ANIMA Corporation). The measured force was changed to torque by multiplying the length of lower leg, and normalized by the body weight (Nm/kg)14 ) . Two self-report questionnaires were used, the Japanese version of the Euro QOL (EQ-5D)15 ) and the 25-question Geriatric Locomotive Functional Scale (GLFS-25)16 ) , with participants completing the questionnaire independently.…”
Section: Methodsmentioning
confidence: 99%
“…Knee extension strength was measured using a hand-held dynamometer (μ-TAS F-1; ANIMA Corporation). The measured force was changed to torque by multiplying the length of lower leg, and normalized by the body weight (Nm/kg)14 ) . Two self-report questionnaires were used, the Japanese version of the Euro QOL (EQ-5D)15 ) and the 25-question Geriatric Locomotive Functional Scale (GLFS-25)16 ) , with participants completing the questionnaire independently.…”
Section: Methodsmentioning
confidence: 99%
“…Grip strength and knee extension strength were measured using handheld dynamometers (T.K.K5401; Takei Scientific Instruments, Tokyo, Japan; and μ‐tus F‐100; ANIMA, Tokyo, Japan). A previous validation study showed that interrater reliability of isometric knee extension strength measurements was highly correlated with the data measured by the handheld dynamometers (intraclass correlation coefficient: men and women = 0.99, respectively). Gait speed was measured using a stopwatch in time units of 0.01 s. Participants were asked to walk straight ahead for 11 m at their usual walking speed.…”
Section: Methodsmentioning
confidence: 99%
“…The intraclass correlation coefficients, used to characterize the reliability of the strength tests using the handheld dynamometer, ranged from 0.84 to 0.99, which is considered good 39 , 40 ) . Furthermore, use of a handheld dynamometer provides a reliable and valid means of measuring muscle strength in patients with brain damage 41 , 42 , 43 , 44 ) .…”
Section: Methodsmentioning
confidence: 99%